Efektifitas Modul Cara Mudah Dan Simpel Belajar Nahwu Dalam Meningkatkan Hasil Belajar Santri Kelas 2 Madrasah Diniyyah Pada Mata Pelajaran Nahwu Di Pondok Pesantren Roudlotul Qur’an Darul Falah III Jombang - Muhammad Rosyid; Haniffudin (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
Student learning outcomes can be improved with various learning methods and strategies. Including among them is the Easy and Simple Way to Learn Nahwu Module Hanifida Method. Researchers are interested in knowing the effectiveness of the Easy and Simple Way to Learn Nahwu Module Hanifida Method in Improving the Learning Outcomes of Class 2 Students of Madrasah Diniyyah in Nahwu Lessons at the Roudlotul Qur'an Darul Falah III Islamic Boarding School, Jombang. There are three formulations of the problem in this study, namely 1) How is the implementation of learning using the module on easy and simple ways to learn nahwu using the Hanifida method in class 2 of the Islamic boarding school of Roudlotul Qur'an Darul Falah III, 2) How are the learning outcomes of students in class 2 of the Islamic boarding school of Roudlotul Qur'an Darul Falah III, 3) How is the effectiveness of learning using the module on easy and simple ways to learn nahwu using the Hanifida method in improving the learning outcomes of students in class 2 of the Islamic boarding school in the nahwu subject at the Roudlotul Qur'an Darul Falah III Islamic Boarding School. This study uses a quantitative approach. This quantitative research is intended to understand the phenomenon of what happens in the educational environment related to learning outcomes. The design of this study uses pretest-posttest values ​​using the help of the SPSS version 25 application. Based on the research results, it can be concluded that the use of the easy and simple way to learn nahwu module using the Hanifida method is quite effective in improving the learning outcomes of class 2 students of Islamic boarding schools in nahwu lessons at the Roudlotul Qur'an Darul Falah III Islamic Boarding School in Jombang